Iron modulates barrier integrity and stem cell function of small intestine during experimental colitis - Wang, Shubin; Yang, Xiangjie; Liu, Xiangjun; Wen, Qin; Xu, Lu; Feng, Mei; Lang, Jinyi; Liu, Dengqun (Frontiers in Nutrition, 2025)
BackgroundUlcerative colitis (UC) brings inconvenience to many patients with inflammatory bowel disease (IBD). Although colonic pathology is widely investigated, little attention has been paid to the disorders in small intestine of UC. In this study, we investigated the impairments of UC to small intestine and further explored how iron metabolism regulated epithelial integrity and the activity of intestinal stem cells (ISCs).MethodsMice were treated by 2.5% dextran sulfate sodium (DSS) for 7 days to established acute experimental colitis. Small intestinal tissues were collected at different time points in the process of DSS-induced colitis. Histological analysis was used to evaluate the changes of small intestine, including H&E, Alcian blue and PAS staining, immunostaining, and qRT-PCR. Iron content was modulated by the supplementation of ferric citrate or depletion by deferoxamine (DFO). The influence of iron on the barrier integrity and stem cell function was further determined by histology, IEC-6 cell, and enteroid culture. ROS content was demonstrated by DHE staining. The proliferation of intestinal stem cells (ISCs) was shown by BrdU and Olfm4 staining, and Lgr5-tdTomato mice were used for lineage tracing study.ResultsIt was shown that during DSS-induced colitis, small intestine underwent a serious injury process, including dysregulated integrity and decreased proliferation of ISCs. Iron overload significantly exacerbated intestinal injury in tissues, epithelial cell line, and intestinal organoids. However, iron chelation by deferoxamine (DFO) would greatly suppress small intestinal injury. Mechanistically, iron overload exacerbated the generation of ROS and enhanced the infiltration of immune cells. In addition, STAT3 and ERK pathways in intestinal epithelium were impaired during experimental colitis, and iron content significantly interrupted the expression of p-STAT3 and p-ERK1/2 within small intestine.ConclusionIn summary, this study proved that small intestine was also impaired in experimental colitis, and iron content could affect DSS-induced small intestinal damage and regeneration, indicating the strategy of iron supplementation in clinical practice needs to be more cautious and consider more factors.